Promotion of healthy lifestyle and its impact on the socio-economic condition of the country and regions - N. Y. Goncharova; A. S. Zadvorny (Путеводитель предпринимателя, 2020)
The article discusses the healthy lifestyle of the population, the factors determining the health of the population, the dynamics of development of physical culture and sports in Russia in 2008, which is an important aspect of economic.